The tree that bends : discourse, power, and the survival of the Maskókî people - Wickman, Patricia R. (Patricia Riles) (University of Alabama Press, 1999)
"In her compelling and controversial arguments, Wickman rejects the myths that erase Native Americans from Florida through the agency of Spaniards and diseases and make the area an empty frontier awaiting American expansion. Through research on both sides of the Atlantic and extensive oral history interviews among the Seminoles of Florida and Oklahoma, Wickman shatters current theories about the origins of the people encountered by the Spaniards and presents, for the first time ever, the Native American perspective. She describes the genesis of the groups known today as Creek, Seminole, and Miccosukee - the Maskoki peoples - and traces their common Mississippian heritage, affirming their claims to continuous habitation of the Southeast and Florida. Her work exposes the rhetoric of conquest and replaces it with the rhetoric of survival."--Jacket